"That Is So Common Everyday . . . Everywhere You Go": Sexual Harassment of Workers in Assisted Living. (April 2018) - Burgess, Elisabeth O.; Barmon, Christina; Moorhead, James R.; Perkins, Molly M.; Bender, Alexis A.
In assisted living (AL) facilities, workers are intimately involved in the lives of residents. Existing research on AL demonstrates the imbalance of this environment, which is a personal home for the residents and a workplace for staff. Using observational and interview data collected from six AL facilities, this grounded theory project analyzes how AL staff define, understand, and negotiate sexual comments, joking, and physical touch. We developed a conceptual model to describe how such harassment was perceived, experienced by AL workers, and how they responded. Sexualized behavior or harassment was experienced by workers of every status. We found that words and actions were contextualized based on resident and worker characteristics and the behavior. Staff members refused to engage residents, redirected them, or reframed the words and gestures to get the job done. Reporting the incidents was less common. We conclude by discussing implications for policy and research.